2011
DOI: 10.1111/j.1469-7610.2011.02510.x
|View full text |Cite
|
Sign up to set email alerts
|

Fathering and mothering in the family system: linking marital hostility and aggression in adopted toddlers

Abstract: Background Previous studies have linked marital conflict, parenting, and externalizing problems in early childhood. However, these studies have not examined whether genes account for these links nor have they examined whether contextual factors such as parental personality or financial distress might account for links between marital conflict and parenting. We used an adoption design to allow for a clear examination of environmental impact rather than shared genes of parents and children, and assessments of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 57 publications
3
54
0
1
Order By: Relevance
“…Similarly, mothers who report past or current antisocial behavior are more likely to behave in a hostile manner toward their infants (Bosquet & Egeland, 2000) and to demonstrate higher levels of harsh discipline toward preschool-aged children (Jaffee, Belsky, Harrington, Caspi, & Moffitt, 2006). Prior research in the current sample also found a link between adoptive parent antisocial personality traits, marital hostility, and hostile parenting during early childhood (Stover et al, 2012). Taken together, these studies provide strong support for the role of parental antisocial behavior in negative parenting during early childhood.…”
supporting
confidence: 58%
“…Similarly, mothers who report past or current antisocial behavior are more likely to behave in a hostile manner toward their infants (Bosquet & Egeland, 2000) and to demonstrate higher levels of harsh discipline toward preschool-aged children (Jaffee, Belsky, Harrington, Caspi, & Moffitt, 2006). Prior research in the current sample also found a link between adoptive parent antisocial personality traits, marital hostility, and hostile parenting during early childhood (Stover et al, 2012). Taken together, these studies provide strong support for the role of parental antisocial behavior in negative parenting during early childhood.…”
supporting
confidence: 58%
“…In contrast, when parents are dissatisfied with their marital relationship, the resulting negative emotion and behavior may transfer to the parent-child interactions (Erel & Burman, 1995). Indeed, numerous previous studies have shown a spillover between marital relationship and parenting (Chang, Lansford, Schwartz, & Farver, 2004;Cui & Conger, 2008;Stover et al, 2012). For example, using data from 158 mothers with elementary-school children in Hong Kong, Chang and colleagues (2004) found that marital quality were significantly and negatively associated with harsh parenting.…”
Section: Marital Satisfaction As a Moderatormentioning
confidence: 83%
“…Using the current sample, the first assessed relationships among marital conflict, parental harsh discipline, and childhood anger/frustration in a sample of toddlers 11 and found an indirect relationship from marital conflict at child age 9 months to child anger/frustration at 18 months via parental harsh discipline. The second, also using the current sample, examined the spillover of marital to parenting hostility to child aggression for both mothers and fathers when children were 27 months old 12 . Results indicated a significant unique contribution of spillover from marital hostility to parenting hostility to child aggression for both adoptive mothers and adoptive fathers.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective financial strain has been associated directly with marital hostility and indirectly to poor parenting through marital hostility. 12,20 Parental traits also have been linked to marital and parenting behaviors. Studies have indicated parental antisocial traits in particular contribute to negative marital and parenting behaviors.…”
Section: Introductionmentioning
confidence: 99%